Role of employer branding dimensions on employee retention: Evidence from educational sector - Noor Ul Hadi; Shahjehan Ahmed (Administrative Sciences, 2018)
Owing to a "War for Talent" every organization is struggling for the best employer status. Thus, attracting, recruiting and retaining talented human capital is the primary focus of every organization. In this regard the aim of the present study is to answer the most frequent and recently asked question of what value(s) organization focus on the retention of their workforce? In so doing, Social Learning Theory and Reciprocity Theory were used as a theoretical background; to further proceed with the study, data was purposively collected from 204 respondents from educational institutes of Pakistan. Findings of the study revealed that development value has a substantial relationship with employee retention. Since, development of new knowledge and skills results in the improvement of one's present job. Furthermore, limitations and implications of the study are discussed.
Keywords: 350; employer branding; employee retention; education sector; development value